VARY : das Trendmagazin für die Generation Queer. (Berlin : VARY Richter Medien Verlag, 1999)
Fonds Suzan Daniel (FSD)
Periodiciteit: tweemaandelijks
Redactie: Fasanenstrasse 38, 10719 Berlin
Duits
Periodiek